Caregiver and provider perspectives on developmental services for children with sickle cell disease: a mixed methods analysis - Tamboli, Mollie; MacArthur, Erin; Collins, Natalie; Kang, Eunyoung; Fernandez, Maria; Porter, Jerlym S.; Conklin, Heather M.; King, Allison A.; Hankins, Jane S.; Heitzer, Andrew M. (Frontiers in Pediatrics, 2025)
IntroductionSickle cell disease (SCD) is a monogenic blood disorder characterized by neurodevelopmental delays. Most children with SCD do not receive developmental services due in part to disparities in care access. To inform the design of a developmental intervention for children with SCD, we evaluated factors that influence access to developmental services.MethodsInterview data were collected from educational and medical providers (n = 15) and caregivers (n = 15) of children aged 4–6 years with SCD at a single center and the surrounding area. Caregivers completed questionnaires about their child's background/medical history, caregiver depression (PROMIS SF v1.0-8a), and caregiver knowledge of early development (Knowledge of Infant Development Inventory). A convergent design was used to integrate the qualitative and quantitative data.ResultsWe identified three themes as factors that influence caregivers' access to developmental services: quality of medical and educational experiences, caregiver knowledge and beliefs about SCD and development, and caregiver preferences for developmental services. Most caregivers denied barriers to obtaining developmental services for their child, whereas providers acknowledged numerous barriers for families. Caregivers and providers shared that a positive caregiver-provider relationship facilitates access. Caregivers reported that there was limited attention to SCD within the hospital system and broader society. Caregivers displayed limited knowledge of early development, and providers identified these knowledge gaps as a barrier to utilizing developmental services. Caregivers expressed a strong interest in SCD education and community building.ConclusionsOur mixed method analysis identified barriers and facilitators to developmental services for children with SCD.